2014
DOI: 10.1103/physrevd.90.114508
|View full text |Cite
|
Sign up to set email alerts
|

Extracting the electromagnetic pion form factor from QCD in a finite volume

Abstract: We consider finite volume effects on the electromagnetic form factor of the pion. We compute the peudoscalar-vector-pseudoscalar correlator in the ϵ expansion of chiral perturbation theory up to the nextto-leading order and find a way to remove the dominant part, which comes from a contribution of the pion zero mode. Inserting nonzero momentum to relevant operators (or taking a subtraction of the correlators at different time slices), and taking an appropriate ratio of them, one can automatically cancel the ze… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Also first steps towards calculating higher n -point functions in the -regime have been taken. For instance the electromagnetic pion form factor in QCD has been calculated to NLO in the -expansion, and a way to get rid of the pion zero-momentum part has been proposed [ 292 ].…”
Section: Low-energy Constantsmentioning
confidence: 99%
“…Also first steps towards calculating higher n -point functions in the -regime have been taken. For instance the electromagnetic pion form factor in QCD has been calculated to NLO in the -expansion, and a way to get rid of the pion zero-momentum part has been proposed [ 292 ].…”
Section: Low-energy Constantsmentioning
confidence: 99%
“…Also first steps towards calculating higher n-point functions in the -regime have been taken. For instance the electromagnetic pion form factor in QCD has been calculated to NLO in the -expansion, and a way to get rid of the pion zero-momentum part has been proposed [341].…”
Section: Correlation Functions In the -Regimementioning
confidence: 99%
“…Finally, the effect of non-zero modes are non-negligible on our small lattice [21]. We estimate its size as 8%.…”
Section: Pos(cd15)016mentioning
confidence: 83%
“…Second, the dispersion relation may be distorted in the ε regime. By an estimate at the next-toleading order ChPT, it can be shown that a distortion of the form E(p) → √ p 2 + Z m m 2 π with Z m ∼ 2 is expected [21]. Since the relation E(p) → √ p 2 + m 2 π is used when constructing R 1 V , as given in Eq.…”
Section: Pos(cd15)016mentioning
confidence: 99%
See 1 more Smart Citation